PENGARUH STRUKTUR VEGETASI TERHADAP KELIMPAHAN KERANG BAKAU (Polymesoda erosaLightfoot 1786) PADA MUSIM KEMARAU DI KAWASAN HUTAN MANGROVE SEGARAANAKAN CILACAP - M. Sofwan Anwari; Su narto; Dul bahri; Suwarno Hadisusanto (Universitas Tanjungpura, 2013)
The aim of this research is to analysis the effect of vegetation structure on abundance of mangrove clam (Polymesoda erosa Lightfoot 1786) at dry season in mangrove forest of Segaraanakan Cilacap. This forest has a degradation area from 17.090 hectare to 9.272 hectare because of illegal logging on mangrove vegetation. The degradation of mangrove vegetation will cause on degradation on mangrove clams. Method of the research was stratified purposive sampling based on mangrove. vegetation The results of research showed that from cubic regression analysis the mangrove saplings vegetations has no effect onthe abundance of mangrove clams, vice versa, the mangrove seedlings has an effect onthe abundance of mangrove clams. Bio-environment analysis results indicate that mangrove seedlings which influence to mangrove clams abundance were Acanthu sebrateatus, Avicennia marina, Acrostimum speciosum and Sonneratia alba. Keywords: abundance, mangrove clam, structure vegetation Segaraanakan Cilacap.